Digital droplet LAMP as a microfluidic app on standard laboratory devices. Issue 13 (15th March 2016) - Schuler, Friedrich; Siber, Clara; Hin, Sebastian; Wadle, Simon; Paust, Nils; Zengerle, Roland; von Stetten, Felix
Abstract : Digital droplet LAMP is performed on a disposable chip (DropChip) with the size of a microscope slide using only standard laboratory devices. Abstract : Digital nucleic acid amplification methods are a growing research field that allows for absolute quantification of DNA making the need of standard curves redundant. However, most of the existing digital amplification systems require specialized laboratory devices and costly investments. The required disposable cartridges are device specific and not interchangeable. Here, we present digital droplet loop-mediated isothermal amplification (ddLAMP) as a microfluidic app on standard laboratory devices. ddLAMP is implemented on a disposable polymer chip (DropChip) in the format of a standard microscope slide. After off-chip DNA denaturation, the reaction mix is emulsified in the DropChip in a mini centrifuge for 6 minutes. The DropChip is transferred to an in situ thermal cycler for 1 hour of incubation. Afterwards, a fluorescence scan in a microarray scanner is performed. The DropChip allows for absolute quantification with a dynamic range of 15–1500 DNA copies per μl. Assay conditions were optimized for ddLAMP and comparison of ddPCR and ddLAMP for genomic E. coli DNA reveals very good concordance.